Preceptor of dentistry and its role in health professional training: a phenomenological study (Research, Society and Development, 2020)
The role of the Preceptor is reflected in mediating the teaching-learning process and also being responsible for inserting the academic in the social reality of the internship field in the public service. However, the distance between the training university and the Preceptor, has negative effects on the education of dentistry students. Therefore, this research aims to discuss the role of Dentistry preceptorship in the emergency department of a public hospital in the city of São Gonçalo / RJ. This is a qualitative, phenomenological study conducted with 8 dentistry preceptors. The method suggested by Amedeo Giorgi was followed and the data analysis was conducted through interviews in the light of Merleau-Ponty's phenomenology. Two categories emerged in this study: Perception of the preceptor dentist within the healthcare team and The preceptor and the understanding of his role in the formation of the dental student. The university's relationship with the professional preceptor enables the academic to gain a better knowledge of social reality and to train a professional with social involvement and knowledge of the real needs of the population.